A2.31 Braf (v raf murine sarcoma viral oncogene homologue B1) mutations in rheumatoid arthritis patients. (13th February 2015) - Arnoux, F; Lambert, N; Fina, F; Martin, M; Kanaan, S; Balandraud, N; Auger, I; Roudier, J
Abstract : Background: Rheumatoid arthritis (RA) is a chronic autoimmune disease characterised by excessive immune responses resulting in inflammation of the joints. Braf (v raf murine sarcoma viral oncogene homologue B1), a kinase of the mitogen-activated protein (MAP) kinase cascade known to regulate cell activation, may be involved in inflammation. By using an assay capable to detect one mutated cell out of 1000, we found that BRAF is mutated in 1% of peripheral blood cells of 23/45 RA patients. In most patients the valine residue at position 600 is substituted by an alanine (V600A). In this study, we evaluated the frequency of V600A mutation in RA patients and controls and its effect on Braf kinase activity. Materials and methods: A digital droplet polymerase chain reaction (0.001% sensitivity) was used to detect V600A mutation in 110 RA patients and 127 controls including 43 healthy controls, 31 patients with other autoimmune diseases (lupus and scleroderma) and 53 patients with other inflammatory diseases (spondylitis ankylosing and psoriatic arthritis). To test whether V600A influences Braf kinase activity, we developed an in vitro phosphorylation assay of MEK1 (mitogen extracellular regulated kinase), a major Braf substrate. MEK1 phosphorylation was tested in presence of wild type or mutated recombinant Braf proteins. Results: We found that 54% of patients with RA have a V600A BRAF mutation versus 26% of controls (p = 0.00001). When we looked at the number of mutated cells it appeared that patients with RA had more V600A mutated cells than controls. Moreover, we found that V600A activates in vitro phosphorylation of MEK1. Conclusions: Most RA patients have V600A mutation in BRAF gene. This mutation is a strong enhancer of Braf kinase activity. V600A mutation could activate the MAP kinase pathway through Braf, leading to pro inflammatory cytokine production and joint inflammation.